Icon and hermeneutics of the image. A reading by Hans Belting - Fernández Uribe, Carlos Arturo (Estudios de Filosofía, 1997)
Hans Belting propases a new way of considering the icon, way which is here called ''historie narrative". This ingenious perspective, clase in a sense to the hermeneutic approach, leads to understand the meaning of iconography priorto that ofthe Age of Art, starting from its historical, social and political contexts. Concerning particularly Byzantine Art, directed towards cultural praxis, this view excels the History of Art sphere, in sofar as it permits to understand the evolution of religious beliefs, out oftheir mere aesthetic value.